A Study on Banking Habits of Rural Students in Udupi District - H, Santhosh Naik (IJRDO - Journal of Business Management, 2023)
As banking is the most progressive industry in the recent years. The Economic Development of the nations largely depends on the growth of banking sector. Therefore, it has its own significance. When financial inclusion is one of the main agenda of the government and our prime minister announces Pradhan Mantri Jan Dhan Yojana which encourages even the poorest rural citizens of India to get banking services with opening banking account . At that time many people have opened their bank accounts with zero balance and they started to make savings and getting the benefit of banking services. The Rural people are having less income have made lessor savings and made lesser transactions in banking sector. But banking habits helps them in various ways and made lesser transactions in banking sector. But banking habits helps them in various ways and encourages them to save more to use the same during needy periods and also get interest for their savings. This study focuses on analyzing the banking habits of the rural studens residing in Udupi District. Banking habits is a pattern of behavior of people in banking transactions. It includes analyzing the respondents, frequency of bank branch visits, nature accounts and transactions carried out by them etc. This study analyse the data collected from 100 respondents residing in Udupi District. In geographical terms the study limits itself in Udupi. This study has concluded that awareness about and satisfaction of the rural students for banking services lead s to improvement of banking operations.